SUKU ADAT DAN TRADISI BERDASARKAN KETERUNUNAN DI TENGAH-TENGAH PEMERINTAHAN BERKEDOK KERAJAAN - Endah Meilani Sari; Aditya Candra Pratama Sutikno (JBI : Jurnal Bahasa Indonesia, 2023)
Environmental and cultural conditions, being the spectrum of offense "clan", the marriage of an indigenous kingdom with the customs and traditions of ancestors. Law becomes the basic reference of an action from the habit of a legal practice. The description of a legal event becomes a fact from a test of study, Kinship law becomes the orientation of giving birth to customs and traditions of a tribe. Research aims to provide a complete picture of social settings or intended for exploration and clarification of an event or social event by describing a variable related to the problem and the terms of a study on the subject of orientation. Marriage becomes an important part of a legal act, and offspring becomes one of the sagas in every human life.